OPAQUE FINANCIAL REPORTS AND STOCK PRICE CRASH RISK IN INDONESIA - Purwoto, Lukas; Tandelilin, Eduardus (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
Stock price crash risk is explained in perspective of corporate governance which refers to the lack of information disclosure. This research investigates the effects of opaque financial reports on stock price crash risk of Indonesia-listed firms from 2005 to 2008.The results show that the degree of crash risk is high. Analyses of binary outcome models, which are controlled by company characteristics, show that crash risk is higher in firms with more opaque financial reports. These results of analysis validate the findings of Hutton et al. (2009) so consistent that insiders or managers hide bad news or negative information when submitting poor financial reports.